LncRNA PSMA3-AS1 promotes preterm delivery by inducing ferroptosis via miR-224-3p/Nrf2 axis: The role of lncRNAs in premature delivery - Qiu, Liyin; Lin, Xiaoqian; Chen, Ruiyun; Wu, Yiting; Yan, Jianying (Cellular and Molecular Biology, 2023)
Long non-coding RNAs (lncRNAs) have a vital potential in premature delivery. This research was intended to explore PSMA3-AS1’s role in premature delivery as well as its possible molecular mechanism. We enrolled 100 premature delivery patients and 100 term patients. Fetal membranes were collected. RT-qPCR was adopted for evaluating PSMA3-AS1, miRNA-224-3p, along with Nrf2 expression. Cell function experiments were implemented to clarify PSMA3-AS1 functions in human trophoblast HTR-8/SVneo cells. Rescue together with mechanistic experiments were implemented for assessing the regulatory function and interaction between miR-224-3p and PSMA3-AS1 or Nrf2 axis in human trophoblast cells. The results uncovered that PSMA3-AS1 level presented downregulation in the fetal membrane tissues and human trophoblast cells. Overexpressed PSMA3-AS1 enhanced cell proliferation but suppressed ferroptosis in human trophoblast cells. Besides, PSMA3-AS1 elevation also attenuated the LPS-induced inflammatory response and restored the LPS-induced upregulation of 20α-HSD and downregulation of progesterone (P4). Mechanistically, miR-224-3p could bind to PSMA3-AS1 and present upregulation in fetal membranes and human trophoblast cells. Notably, overexpressed miR-224-3p offset the influences of PSMA3-AS1 on human trophoblast cell proliferation and ferroptosis. Furthermore, Nrf2 was targeted by miR-224-3p. Downregulated Nrf2 offset the influences of the miR-224-3p inhibitor and induced HTR-8/SVneo dysfunction. Additionally, Nrf2 transcriptionally activated PSMA3-AS1 and GPX4. In conclusion, PSMA3-AS1 expression is low during premature delivery and overexpressing PSMA3-AS1 promotes proliferation and suppresses ferroptosis of human trophoblast cells by interacting with miR-224-3p to downregulate Nrf2. Therefore, enhancing PSMA3-AS1 expression may be a promising therapeutic strategy to prevent premature delivery.